Implications of parent and child quality of life assessments for decisions about growth hormone treatment in eligible children. Issue 6 (7th January 2013) - Otero, S. C.; Eiser, C.; Wright, N. P.; Butler, G.
Abstract Objective To determine differences between parents and children in ratings of child health‐related quality of life (HRQL) prior to growth hormone treatment. Method HRQL measures were collected from 144 children and their caregivers. Inclusion criteria were aged between 10 and 16 years, diagnosed with Turner's syndrome, acquired or idiopathic growth hormone deficiency (AGHD or IGHD) and eligible to begin human GH treatment (GHT), or non‐growth hormone deficient (GHD) short stature. Results Parents rated children to have poorer physical and psychosocial HRQL than children rated themselves. Differences depended on the measure used. Parents rated children with IGHD and non‐GHD short stature better than children rated themselves, but they rated children with AGHD or Turner's much worse than children rated themselves in terms of physical but not psychosocial functioning. Conclusions Decisions to prescribe GHT should include children's perspectives of HRQL whenever possible. Differences between parents and children are most likely in conditions that involve more complex medical needs (AGHD and Turner's). Generic and disease‐specific HRQL measures may vary in sensitivity to HRQL differences between groups. More work is required to evaluate HRQL among younger children.